Trichospilus Diatraeae Cherian & Margabandhu, 1942 (Hymenoptera: Eulophidae), un nuevo parasitoide de Hypsipyla Grandella (Zeller, 1848) (Lepidoptera: Pyralidae) - Zache, Bruno [UNESP]; Wilcken, Carlos Frederico [UNESP]; Zache, Ronelza R. C. [UNESP]; Soliman, Everton P. [UNESP]; Roman, Lorena San [UNESP] (My University, 2010)
Primer reporte de Trichospilus diatraeae (Hymenoptera: Eulophidae) parasitando pupas de lagarta Hypsipyla grandella, principal plaga forestal en América Latina y el Caribe, abriendo nuevas perspectivas para la utilización de este parasitoide en programas de control biológico de lagartas de importancia forestal.

This is the first report of Trichospilus diatraeae (Hymenoptera: Eulophidae) found in the field parasitizing pupae of the Hypsipyla grandella, major forest pest in Latin America and the Caribbean, this offers new perspectives for the use of this parasitoid in biological control programs against caterpillars of forestry importance.
Trichospilus Diatraeae Cherian & Margabandhu, 1942 (Hymenoptera: Eulophidae), a new parasitoid of Hypsipyla Grandella (Zeller, 1848) (Lepidoptera: Pyralidae)